Integrating shared decision making into trial consent: A nested, cluster-randomized trial. Issue 7 (July 2021) - Lipstein, Ellen A.; Breslin, Maggie; Dodds, Cassandra M.; Kappelman, Michael D.; Ollberding, Nicholas J.; Margolis, Peter; Xu, Yingying; Brinkman, William B.
Highlights: Shared decision making can be integrated into trial consent. Shared decision making tools can assist research staff in the consent process. Many potential study participants have trial-related knowledge deficits. Abstract: Objective: Using a nested, cluster-randomized trial, we tested the hypothesis that a shared decision-making intervention, as part of consent, would improve study-related knowledge. Methods: We developed a shared decision-makingintervention then randomized sites in a clinical trial to intervention or control (standard consent). We collected participants' knowledge (primary outcome) and decisional support data. Other data came from a clinical registry and research coordinator surveys. We compared outcomes between study arms using generalized estimating equation models, accounting for clustering. We used qualitative description to understand variation in intervention use. Results: 265 individuals, from 34 sites, enrolled in the parent trial during our study period. Of those, 241 participants completed our survey. There was no knowledge difference between arms (mean difference = 0.56 (95 %CI: -3.8, 4.9)). Both groups had a considerable number of participants with misunderstandings. We also found no difference for decisional support (mean difference = 1.5 (95 %CI: -1.8, 4.8)) or enrollment rate between arms. Clinician use of the intervention varied between sites. Conclusions: We found no differences in outcomes but demonstrated the feasibility and acceptability of incorporating a shared decision-making intervention into consent. Practice implications: Future work should consider adapting our intervention to other trials and more robust measurement strategies.